WHEREVER I GO, I WILL ALWAYS BE A LOYAL AMERICAN (Author: Yoon K. Pak) - Yoshida, Reiko (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 2002)
YOON K. PAK. Wherever I Go, I Will Always Be A Loyal American. New York. NY: Routledge Falmer (2002). 204pp. US21.95, (ISBN 0-415-93235-1).